Employee Engagement, Organizational Citizenship Behavior, dan Supervisi Akademik dalam Peningkatan Kinerja Guru di Sekolah Dasar - Satibi, Imam (Jurnal Kridatama Sains dan Teknologi, 2023)
Employee engagement in the modern era like now is an important problem because of advances in information technology which is also followed by a change in human generation which is dominated by the millennial generation (generation Y) who have different characteristics and attitudes from previous generations (generation baby boomers and generation X). . The purpose of this study was to determine the effect of academic supervision, employee engagement, and Organizational Citizenship Behavior on increasing teacher effectiveness. with the results being very important for improving the quality of teacher performance in Indonesia. The method used is quantitative, namely research based on the philosophy of positivism is used to study certain populations or samples, the sampling method is usually random, research instruments are used in data collection, data analysis is quantitative/statistical in nature and aims to test established hypotheses. The final results of the study illustrate that Academic supervision has no significant effect on teacher effectiveness, staff placement does not have a significant effect on teacher effectiveness. This shows that employee engagement cannot be used as a variable to improve teacher performance, Organizational Citizenship Behavior (OCB) has a significant effect on teacher performance. This shows that Organizational Citizenship Behavior (OCB) can be used as a tool to improve teacher performance, and Academic Supervision, Employee Engagement and Organizational Citizenship Behavior (OCB) together have a significant effect on teacher performance. Keywords: Teacher, Performance, Improvement